A new species of Potentilla (Potentilleae, Rosaceae) from central China, with reference to molecular and morphological evidence - Zhang, Hua-Jie; Zhang, Dai-Gui; Feng, Tao; Liu, Qun; Yang, Jing-Yuan; Chen, Li; Wang, Heng-Chang; Deng, Tao (Phytotaxa, 2021)
Potentilla sunhangii, a new species of Potentilla, from the Jin-hou-ling Mountains, Shen-nong-jia Forest District of Hubei province, China, is described and illustrated. The wild population of the new species is at an elevation of approximately 2930 m and has leaves palmately 3 foliolate. It is morphologically much similar to P. saundersiana, whilst being easily distinguished by its dense array of glands around the plant and green on both surfaces of leaves. Our molecular phylogenetic analysis based on nuclear and chloroplast confirmed the species belongs to Potentilla, in Argentea clade.